Characterizing Incommensurability on the basis of a contextual theory of language - Léna Soler (Philosophia Scientiæ, 2004)
In this article I present, first, a criticism of certain aspects of the way Martin Carrier characterizes semantic incommensurability on the basis of a contextual theory of language. Subsequently I introduce some distinctions and put forward some proposals in order to pursue the same project. It will be argued that two different conceptions of the notion “conditions of applications” and, correlatively, two different meanings of the clause “preservations of the inferential relations”, are involved in Carrier’s characterisation, and that his central tenet holds only thanks to the corresponding meaning-shifts. According to Carrier’s thesis, the incommensurable concepts are those that are untranslatable in the following specific sense: they have either the same conditions of application or the same inferential relations, but they never satisfy both determinants at the same time. I suggest to replace this thesis by a characterisation that, from a methodological point of view, grants logical priority to the inferential relations. This characterisation is mainly based: on one side on the Kuhnian claim that the incommensurable concepts are those who have largely non superimposable inferential relations; on the other side on an analysis of the links between inferential relations and conditions of application, particularly on a reflection concerning the conditions under which some inferential relations can and should be equated with conditions of application.